2013
DOI: 10.1007/s00284-013-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Glutathione in the Lead-Induced Toxicity in Saccharomyces cerevisiae

Abstract: The effect of intracellular reduced glutathione (GSH) in the lead stress response of Saccharomyces cere-visiae was investigated. Yeast cells exposed to Pb, for 3 h, lost the cell proliferation capacity (viability) and decreased intracellular GSH level. The Pb-induced loss of cell viability was compared among yeast cells deficient in GSH1 (Dgsh1) or GSH2 (Dgsh2) genes and wild-type (WT) cells. When exposed to Pb, Dgsh1 and Dgsh2 cells did not display an increased loss of viability, compared with WT cells. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…In a previous work, it was shown that the exposure of S. cerevisiae cells to Pb originated a decrease of GSH [10], which suggested the participation of GSH in Pb detoxification. The results here presented support the involvement of glutathione transferases in Pb detoxification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous work, it was shown that the exposure of S. cerevisiae cells to Pb originated a decrease of GSH [10], which suggested the participation of GSH in Pb detoxification. The results here presented support the involvement of glutathione transferases in Pb detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical differences between WT and each of the ABCC transporters deleted strains were tested using an unpaired t test. The means with asterisks are extremely of significant difference (P<0.001) Taking into account that: (i) GSH is involved in Pb detoxification [10]; (ii) GSTs are involved in Pb detoxification (Fig. 1); (iii) ABCC proteins transport substrates as GSH conjugates rather than transporting the unmodified substrates themselves [19]; and (iv) cells of mutant strains devoid of the ABCC vacuolar transporters Ycf1p, Vmr1p, Ybt1p or Bpt1p displayed an increased susceptibility to Pb (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pb is classified as a priority pollutant by the US Environmental Protection Agency (US-EPA 2006) and can cause, in humans, blood and brain disorders (ATSDR 2007). In the yeast Saccharomyces cerevisiae, Pb inhibits assimilation of nutrients (Chen and Wang 2007) and metabolic activity (Van der Heggen et al 2010), decreases the intracellular level of reduced glutathione (Perez et al 2013) and induces oxidative stress (Bussche and Soares 2011;, DNA damage (Cui and Tang 2000;Yu et al 2009;Yuan and Tang 1999), loss of proliferation capacity (Soares et al 2003;Suh et al 1999) and cell death displaying phenotypic markers of apoptosis (Bussche and Soares 2011). Pb is compartmentalized in the vacuole by two parallel pathways: one dependent of H + gradient generated by the V-ATPAse and another mediated by ABCC transporters (Ycf1p, Vmr1p, Ybt1p and Bpt1p), after conjugation with glutathione, in a process catalysed by glutathione transferases 1 and 2 (Gtt1p and Gtt2p) (Sousa et al 2015).…”
Section: Introductionmentioning
confidence: 99%